Performance Measurement of Data Transfer Services in MAP - Weaver, Alfred; Strayer, Timothy (University of Virginia, Department of Computer Science, 1988)
The manufacturing community has adopted the Manufacturing Automation Protocol (MAP) in an attempt to foster standardization and interoperability, but is now justifiably concerned about the responsiveness of MAP protocols when used in time-critical applications. One result of this concern is the emergence of the Enhanced Perfonnance Architecture which provides the application process with direct access to a fast datalink datagram service rather than the more robust virtual circuit service provided by full MAP. We explain the frmctional differences between the two service types and why both are useful in the manufacturing environment. We show that message segmentation makes a substantial contribution to overall message latency. We illustrate how the retransmission timer setting and the maximum credit window size affect performance. We report throughput and end-to-end delay for one implementation of MAP and draw conclusions about the expected performance cost of messages sent as datagrams versus messages sent over virtual circuits. Note: Abstract extracted from PDF file via OCR
Original submission date: 2013-10-11T18:17:35Z